Power Outage Sensing Device based on IOT for Service Quality Evaluation in the PLN Distribution System - Fauzi, Adryan Fahri Zul; Kiswantono, Agus; saidah, saidah (Faculty of Engineering, Universitas Tanjungpura, 2021)
In overcoming electrical disturbances, PLN implements an equipment protection system that aims to reduce the areas experiencing power outage. However, this protection system has not been integrated with the SCADA system. As a parameter to maintain customer service continuity, PLN uses customer-based indexes, i.e., the Customer Average Interruption Duration Index (CAIDI) and Customer Average Interruption Frequency Index (CAIFI). In the calculation of those index values, the record of power outage occurrence at PLN is still not accurate because the duration and frequency of power outage based on customer complaints. In this study, a Power Outage Sensing device is installed on the secondary distribution system transformer 380/220 which can ensure the location, record the frequency and duration of power outage and serve customers in real time based on IOT using WEMOS D1 and optocoupler sensors which can then be accessed on a web. In its implementation, all power outage is recorded in the database and can be accessed on the web interface. This device can speed up the recovery of disturbances in the system after an outage and perform accurate CAIDI and CAIFI index calculations as customer service evaluations.